Microplastics as potential vectors for selected organic chemical pollutants in river ecosystems - Tumwesigye, Edgar (Rhodes University, Faculty of Science, Institute for Water Research)
Microplastics (MPs) as pollutants in river ecosystems have received considerable research attention in recent years. However, in Africa, research on MPs is sparse, and more needs to be done. Empirical evidence suggests that MP can act as vectors of organic chemical pollutants due to their diverse functional groups and other physical-chemical properties, such as their small sizes, crystal structure and porosity. MPs acting as vectors of chemical pollutants, adds to the complexity of understanding the risk posed to both the ecosystem and human health. Regarding the so-called vector effect, the role of seasonality, land use type, adsorption kinetics, and MP properties has yet to receive the necessary research in the literature, especially concerning pharmaceutical active compounds and other organic pollutants in river systems. This is particularly true for Africa, including South Africa. This study, therefore, aimed to fill these existing research gaps. Overall, the study aimed to investigate the potential of selected microplastic polymers of a particular size range as vectors of organic pollutants in urban rivers within the Eastern Cape of South Africa. To achieve this aim, the study explored the influence of spatial-temporal variability, MPs particle sizes, and various physicochemical variables on the adsorption of antibiotics: Sulfamethoxazole, ciprofloxacin, and endocrine disruptors: 17Î²-Estradiol, 4-(2, 6-dimethyl-2-heptyl) phenol. The adsorption kinetics mechanism was also investigated and established. Polyethylene Terephthalate (PET) and polypropylene (PP) MPs were seasonally deployed once in the summer and autumn seasons, i.e. 20th January 2022 in Bloukrans River and 21st January 2022 in Swartkops River for the summer season and 7th April 2022 in Bloukrans River and 8th April 2022 in Swartkops River for the autumn season. Deployed MPs were of two size ranges, type 1 (2 mm<-â‰¤5 mm) and type 2 (0.5mm<-â‰¤2 mm). The sites where the MPs were deployed had different land use practices: informal settlements, discharge points of wastewater treatment works (WWTWs), agricultural farms, and control sites, considered as the least impacted sites. This was done to analyse land use types' role in the adsorption of chemical pollutants onto MPs. MPs were retrieved in periodic intervals of 7 days, 14 days and 35days calculated based on the day of deployment for both summer and autumn seasons and analysed for Sulfamethoxazole, Ciprofloxacin, 17Î²-Estradiol, 4-(2, 6-dimethyl-2-heptyl) phenol using high-resolution liquid chromatography"“mass spectrometry LC-MS/MS equipped with a triple quadrupole (QqQ) analyser. Concurrent with MP retrieval water physicochemical variables: pH, dissolved oxygen (DO), temperature, turbidity, electrical conductivity (EC), total suspended solids (TSS), total dissolved solids, total alkalinity and total hardness. The adsorption kinetics mechanism was studied in the laboratory between PET and PP of two size ranges and Sulfamethoxazole, Ciprofloxacin, and 17Î²-Estradiol model chemical. The results indicate that land use practices significantly impacted the concentration of the adsorbed chemicals on MPs. Sites downstream of the WWTW had higher concentrations of Sulfamethoxazole: 11119.6001Â±12552.4120ngL-1 and ciprofloxacin: 30285.19Â± 28783.7821ngL-1 adsorbed onto MPs in the Bloukrans River compared to the concentration of same compounds from other land use types along the same River catchment. Agriculturally impacted sites had higher concentrations of 17Î²-Estradiol on MPs; 11624.5611 Â± 15382.2923ngL-1 and 100.3635Â± 29.6321ngL-1 in Swartkops and Bloukrans Rivers respectively compared to other sites. These results suggest that land use is an essential factor influencing chemical inputs into rivers and their adsorption onto MPs. Adsorption was higher for the MP of smaller sizes compared to MPs with bigger sizes, indicating that size is an essential factor that influences the vector effects of MPs. Adsorption was significantly higher after 35 days than all other days during the two seasons (P< 0.05). The adoption kinetics data fitted well with the pseudo-second-order model (R2> 0.99), indicating that chemisorption mechanisms may be the rate-limiting step. Data did not fit the intraparticle diffusion model. Both film diffusion and intraparticle diffusion possibly influenced the rate-limiting adsorption step simultaneously. Regarding the relationship between adsorption and water physico-chemical variables, of special interest a positive correlation between total alkalinity, electrical conductivity, total hardness, and total suspended salts (TDS) and the concentration of the adsorbed chemicals was observed. While the relationship between adsorption and dissolved oxygen was negative. The physicochemical variables with a positive relationship with adsorption are indicative of pollution. Therefore, the result suggests that increasing pollution tends to favour higher adsorption. The results in this study highlight the insights on i) the influence of land use on adsorption, ii) the role of exposure duration on adsorption, iii) the influence of seasonality and MP sizes on adsorption iv) relationship between water physicochemical parameters and adsorption as well as v) establishing adsorption kinetic mechanism. These findings are critical to better understanding the so-called vector effects of MPs and the management associated with MPs in river systems and form essential data sets needed in developing effective pollution mitigation strategies that are region-specific.
Keywords: Microplastics -- Environmental aspects; Vector; Adsorption (Biology); Watersheds; Kinetics